1977
DOI: 10.1002/jrs.1250060202
|View full text |Cite
|
Sign up to set email alerts
|

Visible and near‐ultraviolet resonance Raman spectra of photolabile vitamin B12 derivatives with a rapid‐flow technique

Abstract: Resonance Raman spectra, obtained with 5145,4880 and 3638 excitation, are reported for aquo-, methyl-, 5'-deoxyadenosyl-(coenzyme B,,), thiosolfate and cysteinyl cobdamin, of methyl cobmamide, and of Co(XI) cobalamin (Blzr). Laser-induced photodecomposition was held to acceptable levels with a rapid-%ow technique. A rich assortment of corrin ring vibrations are observed above 600 an-', but the frequencies are constant (within *3cm-') for all the derivatives. Some Raman bands show differential enhancement by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
51
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 18 publications
14
51
0
Order By: Relevance
“…The fact that a vibrational mode showing strong enhancement upon laser excitation into the “α-band” is sensitive to isotopic labeling at C10 implies that significant coupling occurs between corrin SA-stretching motion and an LA-polarized electronic transition. Although it had generally been assumed that the corrin-centered vibrational modes mainly involving SA-stretching motion should only couple to SA-polarized electronic transitions, 45,46 our recent DFT-based rR intensity calculations revealed that these modes can in fact also couple to LA-polarized electronic transitions. 48 …”
Section: Results and Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…The fact that a vibrational mode showing strong enhancement upon laser excitation into the “α-band” is sensitive to isotopic labeling at C10 implies that significant coupling occurs between corrin SA-stretching motion and an LA-polarized electronic transition. Although it had generally been assumed that the corrin-centered vibrational modes mainly involving SA-stretching motion should only couple to SA-polarized electronic transitions, 45,46 our recent DFT-based rR intensity calculations revealed that these modes can in fact also couple to LA-polarized electronic transitions. 48 …”
Section: Results and Analysismentioning
confidence: 79%
“…On the basis of these findings, the ~1500 and ~1550 cm −1 features were assigned as vibrational modes that primarily entail stretching motion of the conjugated C–C and C–N bonds oriented along the LA (the LA-stretching mode) and the SA (the SA-stretching mode), respectively. 45,46 In support of these assignments, the ~1550 cm −1 feature was shown to undergo a significant down-shift upon H/D exchange at C10, while the ~1500 cm −1 feature was largely unaffected by this isotopic substitution. 45 However, on the basis of a density functional theory (DFT)-assisted normal mode analysis for methylcobalamin (MeCbl), 47 Kozlowski and coworkers suggested that the frequency of the SA-stretching mode is in fact lower than that of the LA-stretching mode.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…As for porphyrins many corrin ring modes are observed above 600 cm" 1 . However, the striking conclusion beginning to emerge from this work (Salama & Spiro, 1977) is that, for band positions, all derivatives give very similar RR spectra. Thus a change in axial ligand or cobalt oxidation state appears not to change the conformation of the corrin in the ground state.…”
Section: Optical Activitymentioning
confidence: 87%
“…12 Co-alkyl stretching vibrations have been detected by infrared and Raman spectroscopy, [13][14][15][16] and give an indirect indication of the Co-C bond strength. 17,18 Resonance Raman (RR) spectroscopy can provide access to B 12 -containing proteins, [19][20][21] since laser tuning can be used to selectively excite cobalamin vibrations.…”
Section: Introductionmentioning
confidence: 99%